Polemic note in the original text of Panteleimon Kulish’s novel “The Black Council” (The problem of the recipient) - Федорук, Олесь (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
he article deals with the question of attribution – who did P. Kulish mean in the accompanying note to the original text of the novel “Chorna Rada: Khronika 1663 roku” [“The Black Council: Chronicle of 1663”]? In the fragment of the novel, published under the title “Kozackiie Pany” [“The Cossack Gentlemen”] (Moskvitianin, 1846, No. 1), Kulish entered into a polemic, according to him, with “a friend” about the origin of the custom to make the sign of the cross in front of the fire. Kulish’s opponent, who read the manuscript, thought this custom was influenced by Christianity, but the Kulish explained this custom was influenced by pagan belief.The article supports the assumption that Kulish’s unnamed opponent is historian М. Kostomarov. For argumentation, I examine the original (1846) and final (1857) texts of the Ukrainian version of “Black Rada” (where the author directly calls Kostomarov “my friend”), Kulish’s letters to Kostomarov (which contain a discussion about the correlation of Christianity and national character), Kostomarov’s statements under interrogation during the investigation of the Cyril and Methodius Brotherhood (about the discussion with Kulish of the composition of the novel), Kostomarov’s monograph “Ob istoricheskom znachenii russkoi narodnoi poezii” [“On the Historical Significance of Russian Folk Poetry”] (1843) and “Slavianskaia mifologiia” [“Slavic Mythology”] (1847).Also, in the article the sources of the folk legend about the dialog of two fires and the proverb “The holy fire avenges if it is not respected” (these both texts Kulish quoted in order to convince the opponent) are being identified. The first one Kulish found in the Polish folkloristic collection of Lucian Semensky “Podania i legendy polskie, ruskie i litewskie” [“Polish, Ruthenian and Lithuanian Folk Stories and Legends”] (1845), and the second is gotten from Hrygoryi Ilkevych’s book “Halytski prypovidky i zahadky” [“Galician Riddles and Proverbs”] (1841).